Effects of three different stretching techniques on vertical jumping performance - Kirmizigil, B.; Ozcaldiran, B.; Colakoglu, M. (The Journal of Strength and Conditioning Research, 2014)
The aim of this study was to evaluate 3 different flexibility techniques: (a) ballistic stretching (BS), (b) proprioceptive neuromuscular facilitation stretching (PNF) + BS, and (c) PNF + static stretching (SS) on vertical jump (VJ) performance and to determine the most appropriate stretching method during warm-up period before explosive force disciplines. One hundred voluntary male athletes participated in this study. All subjects performed aerobic warm-up (5-minute jog) followed by BS (5 seconds for each stretching exercise), PNF + BS (PNF performed followed by 5 seconds of BS), and PNF + SS (PNF performed followed by 30 seconds of SS) treatment protocol, respectively in the same day. Each stretching treatment was applied for 4 sets bilaterally. In all stretching treatments, lumbar extensor, gluteus maximus, and hamstring muscles were stretched with a single stretching exercise. After a 2-minute brief rest period, participants performed 3 trials of VJ test followed by one of the treatment protocols. Vertical jump performance was evaluated by countermovement jump (CMJ). Participants were divided into 3 groups according to their flexibility and prejump performances after warm-up. For each individual group and the whole group, after all treatments, differences in CMJ values were obtained (p < 0.05). Ballistic stretching increased the VJ performance in the groups with low and average flexibility, poor prejumping performance, and also in the whole group (p < 0.05). Proprioceptive neuromuscular facilitation stretching + BS affected VJ performance in the group of participants with high flexibility (p < 0.05). Proprioceptive neuromuscular facilitation + SS decreased VJ performance in groups of participants with high flexibility, moderate, and high prejumping performance and in whole group (p < 0.05). Ballistic stretching method increased VJ height, therefore seems to be more suitable than PNF + SS and PNF + BS before events that rely on explosive power as a part of warm-up period.